What does nursing consist of - Angerami, Emília Luigia Saporiti; Correia, Francisco de Assis (Revista da Escola de Enfermagem da USP, 1989)
In the present study we started of the meaning of Nursing from etymological viewpoint. We then made an historical survey of Nursing, detecting the main guiding concepts that directed its practice throughout history. We finally approached the notion of Nursing in the light of its plurality.